Trust deficit: A lingering influence affecting Nigeria policy and governance (Singaporean Journal of Business Economics and Management, 2023)
Trust has become a very influential barrier and deficit to the development and implementation of policies and programes in Nigeria. Most Nigerians have become frustrated by inexistence of commitment to duty and the lack of revitalization of governance towards economic prosperity. These unfortunately has led to the inability of government and its agents to address fundamental issues that hinders consistent policy framework, thereby paving way for trust deficit in governance and administration of the state. Leadership capacity no longer exist in the system of governance in Nigeria. Understanding common values that bridge the gap between the have and the have not has become a nightmare, as the unprofessional conduct of some civil servants and political office holders have created room for lack of sincerity and confidence in the nation's public institutions. This study is set to unravel some of the mistrust or trust issues that affects the citizens as it relates to policies and programmes, and why it has become the norm in Nigeria politics and administration. The study adopted content analysis approach in order to gain an indebt understanding of the phenomenon. Two trust deficit theories were analyzed; these are institutional theory and theory-based evaluation approach. The study recommended that government should be sensitive to the plight of the people, by building and sustaining trust related issues. Policies and programmes should be adequately implemented to dis-way the people from suspicion and indifference to government pronouncement.